2020
DOI: 10.5812/ijpbs.96051
|View full text |Cite
|
Sign up to set email alerts
|

The Role and Comparison of Stressful Life Events in Suicide and Suicide Attempt: A Descriptive-Analytical Study

Abstract: Background: In recent years, suicide in Iran has become a growing concern. Although stressful life events (SLEs) are increasing as a global prevalence, suicide attempters (SAs) and the impact and association between suicide and SLEs are poorly understood. Objectives: This study aimed at examining the role and effect of SLEs in suicides and SAs. Methods: This descriptive-analytical study was performed during 2014 to 2016 based on 186 records (through random quota sampling) of suicidal behaviors (SBs), including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 34 publications
(44 reference statements)
2
9
0
Order By: Relevance
“…In Iran, a 20-year trend indicates increased suicidal deaths with an estimated average rate of 9.9 per 100,000 persons per year. It is estimated that 200 years of life lost (YLL) per 100,000 persons are attributed to suicidal behaviors (SBs) and self-inflicted violence in Iran [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Iran, a 20-year trend indicates increased suicidal deaths with an estimated average rate of 9.9 per 100,000 persons per year. It is estimated that 200 years of life lost (YLL) per 100,000 persons are attributed to suicidal behaviors (SBs) and self-inflicted violence in Iran [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Suicide is a complex and multifactorial issue determined by several demographic and low socioeconomic status (SES), mental illness, sociocultural status (SCS), history of SBs, and health systems' performance concerning suicide prevention [5,7]. SES indicators, such as educational level, unemployment, and low income, have been reliably recognized as risk factors for suicide and SB [8].…”
Section: Introductionmentioning
confidence: 99%
“…In Iran, suicide is considered the fifth cause of death [ 12 ]. The incidence rate of suicide has increased over the past decades, especially in East Azarbaijan Province where there are limited studies on the subject [ 13 ]. Iran has a suicide rate between 1.4 and 29.6 per 100,000 population [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…A community health assessment indicated that SB is the most important health problem in Malekan County, East Azarbaijan. A regional SPP was developed and implemented for suicide and SB prevention in the PHC setting during the period 2014–2017 years [ 13 , 16 ]. The findings and implications of this interventional study can be useful for health care systems.…”
Section: Introductionmentioning
confidence: 99%
“…Annually, approximately 1 million people die due to suicide, yet in many settings, most suicide deaths go undetected and these numbers are the tip of the iceberg [2,4]. Suicide rate is usually higher among developed and Eastern Europe and Eastern Meditation, and Islamic countries have lower suicide rates, due to many social and religious aspects and/or lack of effective registry for suicide systems [5,6]. However, based on standard mortality rates for suicide, low-and middleincome and high-income countries have similar rates at 11.2 and 12.7 per 100,000 people, respectively [7].…”
Section: Introductionmentioning
confidence: 99%